Cibremo / Nurul Ain Mustakim … [et al.] - Mustakim, Nurul Ain; Alfarsar, Faten Nur Afiqah; Jamain, Khairul Najzmie; Shadan, Siti Nursyuhada; Shadan, Siti Nuratiqah; Shahril, Juliana (Division of Research and Industry Linkages, 2017)
A modem (modulator-demodulator) is a network hardware device that modulates one or more carrier wave signals to encode digital information for transmission and demodulates signals to decode the transmitted information. It has been commercialized after the growth of surfing internet rate is increase 50.1% in 2016. Cibremo (Circuit Breaker Modem) invents to solve an issue regarding their modem that often broke whenever the lightning struck. This is due to internal failure such as house wiring problem that allows exceed current to flow through home appliances. Cibremo is implanted by using fuse breaker that can be replace whenever it broken at low cost. The fuse will disconnect the supplied voltage from the modem that flows above the current breaker voltage amount.